Co-occurrence of major depressive episode and Post-Traumatic Stress Disorder among survivors of war : how is it different from either condition alone? - Morina, Nexhmedin; Bogić, Marija; Frančišković, Tanja; Kučukalić, Abdulah; Lečić-Toševski, Dušica; Morina, Lendite; Popovski, Mihajlo; Priebe, Stefan; Ajduković, Dean (2013)
Major Depressive Episode (MDE) and Post-Traumatic Stress Disorder (PTSD) have been shown to be the most common mental disorders following traumatic war experiences and to frequently co-occur. This study aimed to identify whether the co-occurence of MDE and PTSD following exposure to war-related experiences is associated with different demographics, exposure to previous traumatic events, and clinical characteristics as compared to MDE and PTSD alone. Using a random walk technique, face-to-face interviews were conducted with randomly selected participants among war-affected community samples in five Balkan countries (n=3, 313) in the years 2006/2007. Current prevalence rates of MDE, PTSD, and suicide risk were assessed using the Mini–International Neuropsychiatric Interview. Levels of general psychological distress, post-traumatic stress, and quality of life were assessed with self-reports. 30.5% of participants met DSM-IV diagnostic criteria for either MDE or PTSD and 9.1% for both disorders. Participants with concomitant MDE and PTSD reported significantly higher numbers of pre-war and post-war traumatic events than participants with PTSD only and higher number of war-related events than those with MDE only (all ps<.001). They had significantly higher levels of general psychological and post-traumatic stress symptoms, a higher suicide risk, and lower levels of quality of life than participants with either condition alone (all ps<.001). Concomitant MDE and PTSD is associated with the experience of different traumatic events and characterized by more general psychological distress than either condition 4 alone. The assessment of concomitant MDE and PTSD can facilitate a better identification of individuals with severe psychopathology and poor quality of life. People with this co-occurrence may require specific health care programs following war.
Projekt MZOS
ENG